O Processo de inclusão social do adolescente em conflito com a Lei no Municipio de Ariquemes - Rondônia - Pulcinelli, Evaldo Paulo de Souza (2011)
This research aimed to analyze the process of the adolescent's social inclusion in conflict with the law in relation to socio-educational measures in open and closed environment, in the municipal district of Ariquemes Rondônia. Investigated the effectiveness of the public policies for the attendance of child and adolescent in conflict with the law, based on the Child and Adolescent's Statute (CAS), taking into account the actuation of government and no government entities, as well as to examine the actions and the structure of attendance to these adolescents, through Municipal Council of the Child and Adolescent's Rights, Protective Council, Public Ministry, Judiciary and of the Organized Civil Society and examine the public policies in the areas of health, education, social work, culture and leisure as prevention vector of the violence and the marginality. The problem consists in frequency of the recidivisms, where the adolescents just change the infracional act, and they continue in the marginality. In the first chapter is made a parallel of the before and after CAS, drawing a brief historic of the beginning of fight for the child and adolescent's rights to the current days, leaving from punishment to socio-educational measures. The second chapter approaches the child and adolescent in the contemporary times, as well as his social vulnerability, the use of drugs and the violence as backdrop for the infracional act. The third chapter presents the functioning of the socio-educational measures for adolescent conflict with the law in the municipal district of Ariquemes-RO, analyzing the effectiveness of measures in respect of the re-socialization of adolescents, questioning the motives of recidivism in a closed system by internment - and therefore the measures in an open system. Concluding with an assessment and perspective future, pointing suggestions that may contribute to the effectiveness of educational measures,as well as prevention of illegal acts.